Violencia física y autoestima en usuarias de la Junta Cantonal de Protección de Derechos del Cantón Santa Rosa año 2021 - Solano Carranza, Flerida Alexandra (Machala : Universidad Técnica de Machala, 2021)
This study has been configured as a highly relevant contribution since it addresses the characteristics of women victims of physical violence and its repercussions on individual, social and family self-esteem. The objective of the study has been to characterize the level of relationship between physical abuse and self-esteem in women victims of violence of the Cantonal Board for the Protection of the Rights of Children, Adolescents and Women of the Santa Rosa canton, in the year 2021. Therefore, carried out a descriptive exploratory approach, starting from the particularities that physical violence presents in women cared for in the Cantonal Board, for the collection of information on the variables of the quantitative approach was used, through the use of structured and statistical instruments that allow the construction of objective criteria of the particularities of the object of study, in this research a total of 32 women users of this administrative body participated.
El presente estudio se ha configurado como un aporte de mucha relevancia puesto que aborda las características de mujeres víctimas de violencia física y sus repercusiones en la autoestima nivel individual, social, familiar. El objetivo del estudio ha sido caracterizar el nivel de relación entre el maltrato físico y autoestima en mujeres víctimas de violencia de la Junta Cantonal de Protección de Derechos De Niñez, Adolescencia y Mujeres del cantón Santa Rosa, en el año 2021. Por lo que se realizó un abordaje de tipo exploratorio descriptivo, partiendo de las particularidades que presentan la violencia física en mujeres atendidas en la Junta Cantonal, para la recolección de información de las variables de se utilizó el enfoque cuantitativo, mediante el uso de instrumentos estructurados y estadísticos que permiten la construcción de criterios objetivos de las particularidades del objeto de estudio, en esta investigación participaron un total de 32 mujeres usuarias de este órgano administrativo
Keywords: VIOLENCIA FISICA; AUTOESTIMA; DERECHO; GENERO